CARET: Chain-Aware ROS 2 Evaluation Tool - Kuboichi, Takahisa; Hasegawa, Atsushi; Peng, Bo; Miura, Keita; Funaoka, Kenji; Kato, Shinpei; Azumi, Takuya (2022 IEEE 20th International Conference on Embedded and Ubiquitous Computing (EUC), 2022)
This paper presents a tool to evaluate the latency of Robot Operating System (ROS) 2 applications called Chain-Aware ROS 2 Evaluation Tool (CARET). ROS 2 is designed to enhance the modularity of real-time robotic applications, including self-driving software such as Autoware. To analyze the performance of ROS 2 applications, CARET supports measurement functionalities for the callback latency, node latency, communication time between nodes, and end-to-end latency. To calculate each latency, CARET provides tracepoints, an architecture file, information on tracepoint connections, and a message tracking functionality. Furthermore, CARET can visualize different types of latency, such as bottlenecks and lost message, to analyze ROS 2 applications. The experimental results demonstrate that CARET can successfully measure the end-to-end latency of Autoware.Universe, which is ROS 2-based self-driving software.